THE THEORITICAL REASONABLY OF BIOLOGY BASED ON CTL TEACHING MATERIAL ON THE ECOSYSTEM MATERIALS FOR SENIOR HIGH SCHOOL CLASS X - DWI YULIANTI PUTRI, AYU (Berkala Ilmiah Pendidikan Biologi (BioEdu), 2013)
Circulating of the teaching material of ecosystem has not met the seven pillars of contextual teaching and learning (CTL), whereas the material is a material related to daily life. The porpouse of this research is to produce biology tecahing material based on CTL on ecosystem and to describe the theoritical reasonably of biology teaching material based on CTL. This research is development research reference to the development of 4D models with the steps are Define, Design, and Develop without Desseminate step. The target of this teaching material of ecosystem based CTL. This research showed that the teaching material developed was declared very decent with the review by 91,69%. Keywords: The oritical reasonably of teaching materials basedon contextual teaching and learning (CTL), ecosystem material, senior high school class X